2014
DOI: 10.1016/j.engstruct.2014.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced concrete and fiber reinforced concrete panels subjected to blast detonations and post-blast static tests

Abstract: Results of an experimental study of reinforced concrete panels under blast detonations are presented. The primary purpose of the tests was to collect data for validating simulation methods for blast loads. The scaled distance ranged from 0.41 m/(kg) 1/3 to 0.57 m/(kg) 1/3 and hence the tests are close-in detonations. Four types of 1.2 m square panels were subjected to blast to investigate the performance of new walls: reinforced concrete (RC) panels; fiber reinforced concrete (FRC) panels without additional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Wang et al (2012) studied the underwater blast performance of foam cores and CFRP sheets which were graded density. Pantelides et al (2014) discovered the performance of FRC wall panel which has a square shape of size 1.2m under blast. Dear et al (2017) tested the air and underwater blast of various polymeric foam and face sheet composite sandwich panels by TNT proportionate charge of 100 kg at 15m stand-off.…”
Section: B Panelsmentioning
confidence: 99%
“…Wang et al (2012) studied the underwater blast performance of foam cores and CFRP sheets which were graded density. Pantelides et al (2014) discovered the performance of FRC wall panel which has a square shape of size 1.2m under blast. Dear et al (2017) tested the air and underwater blast of various polymeric foam and face sheet composite sandwich panels by TNT proportionate charge of 100 kg at 15m stand-off.…”
Section: B Panelsmentioning
confidence: 99%
“…Terrorist attacks on structures may not be eliminated completely, but the effects of these attacks can be mitigated. Several techniques have been developed in recent Fracture Mechanics Applications years for this purpose, such as retrofitting or coating applications [1,2], internal reinforcement [3,4] or geometrical modifications in buildings [5]. It is desirable that mitigation techniques may be applied in both new and existing buildings.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, experimental investigations have been conducted with the objective of improving the blast-resistant performance of concrete slabs, without increasing the concrete strength or the number of reinforcement bars (Morishita et al 2004), and several researchers have reported the good performance of fiber-reinforced cementitious composites (FRCC) (Banthia et al 2004;Lan et al 2005;Coughlin et al 2010;Foglar and Kovar 2013;Ellis et al 2014;Pantelides et al 2014;Castedo et al 2015;Li et al 2016;Luccioni et al 2017).…”
Section: Introductionmentioning
confidence: 99%